Actual drawing of histological images improves knowledge retention. Issue 1 (29th May 2015) - Balemans, Monique C.M.; Kooloos, Jan G.M.; Donders, A. Rogier T.; Van der Zee, Catharina E.E.M.
Abstract : Medical students have to process a large amount of information during the first years of their study, which has to be retained over long periods of nonuse. Therefore, it would be beneficial when knowledge is gained in a way that promotes long‐term retention. Paper‐and‐pencil drawings for the uptake of form‐function relationships of basic tissues has been a teaching tool for a long time, but now seems to be redundant with virtual microscopy on computer‐screens and printers everywhere. Several studies claimed that, apart from learning from pictures, actual drawing of images significantly improved knowledge retention. However, these studies applied only immediate post‐tests. We investigated the effects of actual drawing of histological images, using randomized cross‐over design and different retention periods. The first part of the study concerned esophageal and tracheal epithelium, with 384 medical and biomedical sciences students randomly assigned to either the drawing or the nondrawing group. For the second part of the study, concerning heart muscle cells, students from the previous drawing group were now assigned to the nondrawing group and vice versa. One, four, and six weeks after the experimental intervention, the students were given a free recall test and a questionnaire or drawing exercise, to determine the amount of knowledge retention. The data from this study showed that knowledge retention was significantly improved in the drawing groups compared with the nondrawing groups, even after four or six weeks. This suggests that actual drawing of histological images can be used as a tool to improve long‐term knowledge retention. Anat Sci Educ. © 2015 American Association of Anatomists.